INFLUENŢA FACTORILOR STRESOGENI, ÎN FUNCŢIE DE REACTIVITATE ŞI VÂRSTĂ, ASUPRA UNOR INDICI AI STATUSULUI MORFOFUNCŢIONAL LA BOVINE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2007)
As a result of the research the correlation between the level of contamination by internal parasites in dairy cattle and their reactivity to stress factors was established. On the basis of the completed investigations there were determined the total proteins decreased, and increased number of eosinophyles and bilirubyn’s level in the reactive to stress cattle in comparison with the resistant to stress ones.